The COVID-19 crisis silver lining: interprofessional education to guide future innovation. Issue 5 (2nd September 2020) - Langlois, Sylvia; Xyrichis, Andreas; Daulton, Brittany J.; Gilbert, John; Lackie, Kelly; Lising, Dean; MacMillan, Kathleen M.; Najjar, Ghaidaa; Pfeifle, Andrea L.; Khalili, Hossein
ABSTRACT: Globally, the advent and rapid spread of the COVID-19 virus has created significant disruption to health professions education and practice, and consequently interprofessional education, leading to a model of learning and practicing where much is unknown. Key questions for this ongoing evolution emerge for the global context leading to reflections on future directions for the interprofessional education field and its role in shaping future practice models. Health professions programs around the world have made a dramatic shift to virtual learning platforms in response to closures of academic institutions and restrictions imposed on learners accessing practice settings. Telemedicine, slow to become established in many countries to date, has also revolutionized practice in the current environment. Within the state of disruption and rapid change is the awareness of a silver lining that provides an opportunity for future growth. Key topics explored in this commentary include reflection on the application of existing competency frameworks, consideration of typology of team structures, reconsideration of theoretical underpinnings, revisiting of core dimensions of education, adaptation of interprofessional education activities, and the role in the future pandemic planning. As an international community of educators and researchers, the authors consider current observations relevant to interprofessional education and practice contexts and suggest a response from scholarship voices across the globe. The current pandemic offers a unique opportunity for educators, practitioners, and researchers to retain what has served interprofessional education and practice well in the past, break from what has not worked as well, and begin to imagine the new.